The use of the songs to help children build up vocabulary - Cajamarca Quintuña, Jaime Ramón; Vásquez Loja, Verónica Elizabeth
This monograph emphasizes the importance of the use of songs to help children (7 to 8 years old) build up vocabulary. The authors of this monograph aim to help teachers and students in Gaspar Sangurima elementary school to improve the teaching-learning process of English as a foreign language, providing a booklet containing listening activities to complement the units of the textbook, Enterprise, used in this school. All the listening activities are based on songs. These activities have been clearly and easily explained so that teachers and students will benefit from them. In addition, the authors of this monograph have considered factors such as age, knowledge of the English language, and interests before designing the booklet. The main objective of this project is to incorporate theory and practice to overcome shyness and monotony in the classroom by teaching English through an effective and fun way. Teachers can use this booklet as a tool to improve their methodologies and construct an efficient learning process.